MANFAAT PENGGUNAAN MEDIA SOSIAL INSTAGRAM BAGI ORANG MUDA KATOLIK NUSA TENGGARA TIMUR DI YOGYAKARTA - Gale, Stefanus; Tanureja, Indra Sanjaya; Warsono, Agustinus Tri Edy (Lembaga Penelitian STKIP Widya Yuwana, 2023)
The development of communication technology makes such a big change in the order of human life. Its development has succeeded in making everyone attached to media activities in their daily lives. The purpose of this study is to find out about the motivation and benefits of using instagram social media among young people today as millennial generation in their daily lives. The young people in question are no exception to the Nusa Tenggara Timur Catholic Youth. The approach used in this study is a descriptive qualitative approach with interviews with informants who are the subjects of this study. The results of the study show that Instagram social media makes a very significant contribution to social media users or activists, especially Nusa Tenggara Timur Catholic Youth. As social media activists, the Catholic Youth found many positive benefits such as; looking for information, expanding relationships, entertainment media, media reporting, learning media as well as promotional media and digital marketing